2019
DOI: 10.1103/physrevb.99.161202
|View full text |Cite
|
Sign up to set email alerts
|

Light irradiation induced brittle-to-ductile and ductile-to-brittle transition in inorganic semiconductors

Abstract: The intrinsic brittleness of inorganic semiconductors prevents them from extended engineering applications under extreme condition of high temperature and pressure, making it essential to improve their ductility. Here, we applied the constrained density functional theory to examine the relationship between plastic deformation and photonic excitation in sphalerite ZnS and related II-IV semiconductors. We find that ZnS transforms from a dislocation dominated deformation mode in the ground state to a twin dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 39 publications
6
20
0
4
Order By: Relevance
“…In addition, the energy barrier along the direction is higher than that in the [1][2][3][4][5][6][7][8][9][10] direction, indicating that it is energetically more favorable to glide along [1][2][3][4][5][6][7][8][9][10] direction. This result is in good agreement with previous experimental results [48], indicating the reliability of our calculations.…”
Section: Testing Of Interatomic Potentialsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the energy barrier along the direction is higher than that in the [1][2][3][4][5][6][7][8][9][10] direction, indicating that it is energetically more favorable to glide along [1][2][3][4][5][6][7][8][9][10] direction. This result is in good agreement with previous experimental results [48], indicating the reliability of our calculations.…”
Section: Testing Of Interatomic Potentialsupporting
confidence: 93%
“…In our calculations, we find that the generalized stacking fault energy curve of <11-2>{111} system is asymmetric, while that of the <1-10>{111} system is symmetric. The maximum stacking fault energy of the <11-2>{111} system is about 1.4 J/m 2 , which agrees well with the first principles calculation result (1.1 J/m 2 ) [48]. In addition, the energy barrier along the direction is higher than that in the [1][2][3][4][5][6][7][8][9][10] direction, indicating that it is energetically more favorable to glide along [1][2][3][4][5][6][7][8][9][10] direction.…”
Section: Testing Of Interatomic Potentialsupporting
confidence: 86%
See 1 more Smart Citation
“…[ 8–12 ] However, finding candidates of stretchable semiconductors that have an appropriate bandgap and related electrical performance as well as mechanical and environmental durability has been challenging. [ 13,14 ] For instance, conventional inorganic semiconductors held by ionic or covalent bonds are intrinsically brittle and show only the strain of about 0.1–0.2%, [ 15–17 ] thus easily experiencing mechanical cracks due to the accumulation of fatigue under repetitive deformation, while organic‐based semiconductors are vulnerable to humidity, oxygen, and chemical and thermal stresses, and their inferior electrical properties; [ 18–21 ] therefore, they cannot fulfil the criteria for future deformable semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…The light-modulated deformation mechanism in ZnS and other II-IV semiconductors was further studied by constrained density functional theory (CDFT). 71 Under light illumination, the deformation of ZnS is mainly controlled by twinning compared to a dislocation-dominated deformation mode without illumination. The research also suggested that crystals with more covalent component may exhibit ductility under light illumination such as ZnTe and ZnSe.…”
Section: Plasticity Of Zns In Darknessmentioning
confidence: 99%